(Endogenous) occupational choices and job satisfaction among recent Spanish PhD recipients. Issue 3 (6th June 2016) - Di Paolo, Antonio
Abstract : Purpose: – The purpose of this paper is to analyse differences in overall job satisfaction and specific job domain satisfaction among PhDs employed in different sectors four years after completing their doctorate degrees. The author take job satisfaction as a comprehensive proxy of perceived job quality. The author draw on data from two successive cohorts of PhD graduates from public universities of Catalonia (Spain). Design/methodology/approach: – First, the author estimate covariate-adjusted job satisfaction differentials for PhD holders employed in different employment sectors, namely: university, research institutes, public sector (government and public administration) and private sector. A stepwise inclusion of job-related covariates enables appreciating the underlying mechanisms that that generate the observed job satisfaction differentials across sectors. Second, the author take into account the endogenous sorting of PhDs into different sectors by jointly modelling sector choice and job satisfaction, where the former is assumed to follow a mixed multinomial logit model. Findings: – The results indicate that PhD holders employed outside academic and research jobs are more satisfied with the pecuniary facets of their work, but significantly less satisfied with non-monetary aspects of job quality. The selectivity-corrected job satisfaction differentials highlight the importance of self-selection and confirm that PhD holders suffer a penalisation for working in non-academic occupations, thus revealing the existence of "academic rents". Originality/value: – This is the first paper that presents a systematic and consistent analysis of job satisfaction differentials among PhD holders that work in different types of occupations, taking into account that sector choice is an endogenous variable, potentially related to unobserved traits that affect job satisfaction. The results are rich of policy implications, which are especially relevant in the light of the existing debate regarding the excess of PhD in the labour market of several European Countries and their subsequent risk of underemployment.